Pendampingan Bisnis dengan Konsep Kewirausahaan Sosial pada Perajin Kain Cepuk di Desa Tanglad Nusa Penida - Pertiwi, Ni Luh Gde Ana (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Woven fabric is a cultural heritage that has existed for hundreds of years and continues to develop to this day, becoming a symbol of pride and regional identity. Cepuk fabric craftsmen in Tanglad Village are part of a community that produces traditional fabrics with skills that have existed for a long time. The existence of cepuk fabric craftsmen in Tanglad Village not only reflects the preservation of local culture, but is also the main source of livelihood for many families in the village. Cepuk fabric craftsmen in Tanglad Village, Nusa Penida, have great potential to develop and provide a positive impact on the local community. However, they often face various challenges, such as limitations in financial management, marketing, and development of production capacity. So it takes an understanding and awareness of the importance of doing business planning and bookkeeping. The methods used are observation methods, presentations with powerpoint and training with books and Google Drive face-to-face or offline. This community service activity is carried out with a door-to-door system, aiming that the material is delivered according to the desired target. The results obtained from this community service activity are to make Cepuk Weaving craftsmen increasingly aware of the importance of bookkeeping for their business, and to be able to increase the desire to learn simple bookkeeping so that their business finances can be better controlled. Overall, social entrepreneurship-based business assistance provides double benefits, namely improving the economic welfare of Cepuk weaving craftsmen while supporting the preservation of culture and the environment.